MIR-4421 AS A POSSIBLE MODULATOR OF MAPK/AKT PATHWAY THROUGH ERP29 IN PHARYNGEAL CANCER - Juliana Carron; Carmen Silvia Passos Lima; Gustavo Jacob Lourenço (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: ERP29 gene encodes a chaperone protein essential for protein folding and secretion. Our previous study linked ERP29 inhibition to an increased risk of pharyngeal cancer (PC) and reduced patient survival, possibly due to the binding affinity between microRNA miR-4421 and ERP29 messenger RNA (mRNA). This interaction leads to ERP29 silencing, which may influence PC progression especially by decreasing necrosis and increasing cell migration. However, the precise mechanism underlying this process remains unknown, particularly its impact on well-established signaling pathways such as MAPK/Akt, which are frequently dysregulated in PC and play a critical role in tumor progression, cell survival, and metastasis. Objectives: This study aims to explore the role of miR-4421 and ERP29 in PC survival and progression. Materials and Methods: We first evaluated ERP29 and miR-4421 prognostic value in head and neck cancer patients assessing the Kaplan–Meier Plotter (kmplot.com/analysis/). We used PC FaDu cell line (ATCC) in two different scenarios: FaDu cisplatin (CDDP)-sensitive and FaDu CDDP-resistant (FaDu-R). ERP29 expression was silenced using a specific siRNA. We identified and validated genes modulated by ERP29 in FaDu and FaDu-R cells by TaqMan plate array and quantitative PCR (qPCR), respectively. We tested if miR-4421 inhibitor could reverse ERP29 silencing effect, with gene expression analyzed by qPCR in FaDu and FaDu-R cells. Statistical analysis was performed by t-test using SPSS 21.0 software (SPSS Incorporation, USA). Results: Lower ERP29 (p = 0.03) and higher miR-4421 (p < 0.01) expressions were associated with poor overall survival in head and neck cancer patients. In FaDu cells, ERP29 silencing increased MAPK1 (FC: 2.4, p = 0.03), AKT1 (FC: 17.5, p < 0.01), and JUN (FC: 29.0, p = 0.01) expression when compared to cells expressing ERP29. In contrast, the transfection of miR-4421 inhibitor reverted those effects, decreasing the expression of MAPK1 (FC: 0.6, p = 0.03), AKT1 (FC: 0.1, p = 0.02), and JUN (FC: 0.1, p = 0.02) compared to the negative control. In FaDu-R cells, ERP29 silencing increased SOS1 (FC: 2.2, p < 0.01), MAPK1 (FC: 2.1, p < 0.01), and AKT1 (FC: 2.2, p = 0.04) expression when compared to cells expressing ERP29. Conversely, miR-4421 inhibitor decreased the expression of SOS1 (FC: 0.2, p = 0.03), MAPK1 (FC: 0.4, p = 0.01), and AKT1 (FC: 0.2, p = 0.04) compared to the negative control. Conclusion: Inhibition of ERP29 expression may impact MAPK/Akt pathway, contributing to PC patients’ poor survival. However, these effects could be reversed by inhibiting the binding of miR-4421 to ERP29. Our study enhances the understanding of PC progression and CDDP resistance, and we hope that our findings will aid in the development of targeted therapy for PC patients by ensuring ERP29 expression. Acknowledgements: The study was supported by Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq grant numbers 140019/2020-0, 307944/2022-0, and 408177/2023-3) and Fundação de Apoio ao Ensino e à Pesquisa do Estado de São Paulo (FAPESP grant number 2023/12810-9) - Cancer Theranostics Innovation Center, (CancerThera) (CEPID FAPESP grant number 2021/10265-8).